Research Status in Clinical Practice Regarding Pediatric and Adolescent Bipolar Disorders - Liu, Lu; Meng, Ming; Zhu, Xiaotong; Zhu, Gang (Frontiers in Psychiatry, 2022)
Bipolar disorders (BDs) have high morbidity. The first onset of 27.7% of BDs occurs in children under 13 years and of 37.6% occurs in adolescents between 13 and 18 years. However, not all of the pediatric and adolescent patients with BD receive therapy in time. Therefore, studies about pediatric and adolescent patients with disorders have aroused increased attention in the scientific community. Pediatric and adolescent patients with BD present with a high prevalence rate (0.9–3.9%), and the pathogenic factors are mostly due to genetics and the environment; however, the pathological mechanisms remain unclear. Pediatric and adolescent patients with BD manifest differently from adults with BDs and the use of scales can be helpful for diagnosis and treatment evaluation. Pediatric and adolescent patients with BDs have been confirmed to have a high comorbidity rate with many other kinds of disorders. Both medication and psychological therapies have been shown to be safe and efficient methods for the treatment of BD. This review summarizes the research status related to the epidemiology, pathogenic factors, clinical manifestations, comorbidities, diagnostic and treatment scales, medications, and psychological therapies associated with BDs.